A Regulatory Time Bomb: Can Singapore’s Model Rescue Indonesia’s Gig Economy? - Nindry Sulistya Widiastiani (Faculty of Law Universitas Jenderal Soedirman, 2025)
Platform workers who work through digital applications such as online transportation and delivery services are growing in Indonesia, but their legal status is still unclear. The incompatibility between the platform's work model and conventional labor regulations results in platform workers not receiving legal protection, social security, or recognition of formal employment relationships. This article examines these problems using normative legal research methods and comparative approaches by comparing the Indonesian legal system with Singapore's policies through the Platform Workers Act 2024. The legal materials include laws and regulations, jurisprudence, and related literature. The study results show that Indonesia still relies on inadequate partial regulation to address the protection needs of platform workers. At the same time, Singapore has taken a progressive step by recognizing the status of platform workers as a separate legal entity with fundamental rights, such as social security, the right to form associations, protection against work injuries, and income transparency. The novel finding of this study lies in identifying the hybrid employment model as a feasible and legally sound framework to bridge the gap between full-time employment and independent contracting in Indonesia. This model not only aligns with Singapore’s adaptive regulatory approach but also offers a policy blueprint for equitable protection without undermining digital innovation. The broader implication is clear: without a comprehensive legal reform that institutionalizes hybrid employment, Indonesia risks entrenching a two-tier labor system that perpetuates inequality within its rapidly expanding digital economy.